Design features and data acquisition system of the TAIGA-Muon scintillation array - Ivanova, A; Budnev, N; Chiavassa, A; Dyachok, A; Fedorov, O; Gafarov, A; Garmash, A; Grebenyuk, V; Gress, O; Gress, T; Grishin, O; Grinyuk, A; et al. (Journal of Instrumentation, 2020)
The TAIGA-Muon scintillation array is located in the Tunka Valley. It is a part of the single TAIGA experimental complex. Its construction has started in the summer of 2019. By the autumn of 2019, the first three clusters were installed. We describe the design of the TAIGA-Muon array, the data acquisition (DAQ) sistem, reading and control systems.